2021
DOI: 10.1097/j.pain.0000000000002402
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and functional evidence for gp130/IL6ST-induced transient receptor potential ankyrin 1 upregulation in uninjured but not injured neurons in a mouse model of neuropathic pain

Abstract: gp130 is a critically important regulator of mechanical hypersensitivity after nerve injury. Transient receptor potential ankyrin 1-responsiveness is upregulated after spared nerve injury in uninjured but not injured neurons. gp130 upregulates transient receptor potential ankyrin 1 in uninjured neurons, and this is associated with signatures of neuropathic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 101 publications
1
11
0
3
Order By: Relevance
“…Increasing evidence has suggested that uninjured DRG neurons also play important roles in neuropathic pain and show robust neurochemical and functional changes after nerve injury ( Kalpachidou et al, 2022 ; Obata et al, 2003 ; Pertin et al, 2005 ; Tran and Crawford, 2020 ). Evoked pain hypersensitivities are common and important neuropathic pain manifestations and are mediated by uninjured neurons through the remaining peripheral innervations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence has suggested that uninjured DRG neurons also play important roles in neuropathic pain and show robust neurochemical and functional changes after nerve injury ( Kalpachidou et al, 2022 ; Obata et al, 2003 ; Pertin et al, 2005 ; Tran and Crawford, 2020 ). Evoked pain hypersensitivities are common and important neuropathic pain manifestations and are mediated by uninjured neurons through the remaining peripheral innervations.…”
Section: Discussionmentioning
confidence: 99%
“…Axotomized neurons may exhibit the most profound gene expression changes that are important for regeneration. Nevertheless, neighboring uninjured DRG neurons also show significant functional changes (e.g., hyperexcitability) and contribute to dysesthesia and evoked pain hypersensitivity as a result of the remaining peripheral innervations ( Djouhri et al, 2012 ; Kalpachidou et al, 2022 ; Obata et al, 2003 ; Tran and Crawford, 2020 ). Thus, identifying and differentiating transcriptional changes in injured and uninjured neurons in a cell-type-specific manner will be important to search for new targets for nerve regeneration and pain treatment.…”
Section: Introductionmentioning
confidence: 99%
“…SNI surgery was performed as previously described [ 29 ]. In short, mice were anesthetized by intraperitoneal (i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…8 Furthermore, IL-6 causes mechanical hypersensitivity in mice likely through regulating the expression of mechanotransducing ion channels, such as TRPA1. 168,214,215 Deficiency of IL-6 affects sensory properties of peripheral neurons, and mice with a conditional deletion of the gp130 in Na v 1.8 expressing nociceptive primary afferents (SNS-gp130 2/2 ) exhibit reduced mechanonociception associated with decreased levels of TRPA1 and are protected from mechanical allodynia. 5,168,214,271,272,388 2.1.3.…”
Section: Peripheral Effectsmentioning
confidence: 99%
“…168,214,215 Deficiency of IL-6 affects sensory properties of peripheral neurons, and mice with a conditional deletion of the gp130 in Na v 1.8 expressing nociceptive primary afferents (SNS-gp130 2/2 ) exhibit reduced mechanonociception associated with decreased levels of TRPA1 and are protected from mechanical allodynia. 5,168,214,271,272,388 2.1.3. Spinal cord and brain Interleukin-6 is upregulated in the spinal dorsal horn in different pain conditions and associated with central neuronal sensitization and chronic pain.…”
Section: Peripheral Effectsmentioning
confidence: 99%